Comparative pan-genomic analyses of Orientia tsutsugamushi reveal an exceptional model of bacterial evolution driving genomic diversity. Issue 9 (23rd July 2018) - Fleshman, Amy; Mullins, Kristin; Sahl, Jason; Hepp, Crystal; Nieto, Nathan; Wiggins, Kristin; Hornstra, Heidie; Kelly, Daryl; Chan, Teik-Chye; Phetsouvanh, Rattanaphone; Dittrich, Sabine; Panyanivong, Phonepasith; et al.
Abstract : Orientia tsutsugamushi, formerly Rickettsia tsutsugamushi, is an obligate intracellular pathogen that causes scrub typhus, an underdiagnosed acute febrile disease with high morbidity. Scrub typhus is transmitted by the larval stage (chigger) of Leptotrombidium mites and is irregularly distributed across endemic regions of Asia, Australia and islands of the western Pacific Ocean. Previous work to understand population genetics in O. tsutsugamushi has been based on sub-genomic sampling methods and whole-genome characterization of two genomes. In this study, we compared 40 genomes from geographically dispersed areas and confirmed patterns of extensive homologous recombination likely driven by transposons, conjugative elements and repetitive sequences. High rates of lateral gene transfer (LGT) among O. tsutsugamushi genomes appear to have effectively eliminated a detectable clonal frame, but not our ability to infer evolutionary relationships and phylogeographical clustering. Pan-genomic comparisons using 31 082 high-quality bacterial genomes from 253 species suggests that genomic duplication in O. tsutsugamushi is almost unparalleled. Unlike other highly recombinant species where the uptake of exogenous DNA largely drives genomic diversity, the pan-genome of O. tsutsugamushi is driven by duplication and divergence. Extensive gene innovation by duplication is most commonly attributed to plants and animals and, in contrast with LGT, is thought to be only a minor evolutionary mechanism for bacteria. The near unprecedented evolutionary characteristics of O. tsutsugamushi, coupled with extensive intra-specific LGT, expand our present understanding of rapid bacterial evolutionary adaptive mechanisms.